2016
DOI: 10.24943/cirf4.2016
|View full text |Cite
|
Sign up to set email alerts
|

Risk-related resettlement and relocation in urban areas: Transcripts and Appendices (Site Report IV)

Abstract: I am part of a research team from the Indian Institute for Human Settlements from Bangalore. We are studying the impacts of cyclone Phailin and the related resettlement programmes in Odisha. Is it okay if I could take about 30 minutes of your time for some questions? The material will only be used for research purposes and your identity will not be disclosed to anyone at any point. You can choose not to answer anything that you do not wish to, and you can stop the interview at any point. (Visiting card is shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Decision-making and implementation processes were understood through interviews with key officials and policymakers (n=26), and consultations (n=2 with 45 stakeholders) (Jain 2016a;Malladi et al 2016). Community-level information on experiences, e.g.…”
Section: Methods and Sample Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Decision-making and implementation processes were understood through interviews with key officials and policymakers (n=26), and consultations (n=2 with 45 stakeholders) (Jain 2016a;Malladi et al 2016). Community-level information on experiences, e.g.…”
Section: Methods and Sample Designmentioning
confidence: 99%
“…In situ upgrading is often rejected by public authorities arguing that the community is 'untenable' not because of the presence of a hazard but, rather, because they do not adhere to the minimum development control norms or service level benchmarks . Our research, which looked at decision-making processes and outcomes of such resettlement interventions, showed that low-income households build dwellings and settlements over time, and those who have lived in these locations for several years tend to develop adaptation/ coping strategies to deal with the hazard risks (Malladi et al 2016). We found that the allowable intervention strategies for such slums could be widened, to include in situ redevelopment or slum upgrading, for instance, and resettlement should be avoided since it tends to increase the socio-economic burden on the people, apart from a financial, political and environmental burden on the city at large.…”
Section: Case 2: Indiamentioning
confidence: 99%
See 1 more Smart Citation